Tech meets practice: Shadowing with mobile tools to enhance L2 vocabulary mastery - Purwanto, M Bambang; Yuliana, Yuliana; Nurdianingsih, Fitri; Despita, Despita (Jurnal CULTURE (Culture, Language, and Literature Review), 2025)
Vocabulary acquisition plays a crucial role in mastering English as a foreign language (EFL), yet numerous learners face challenges in expanding their lexical repertoire and applying it accurately. This research investigates how shadowing techniques delivered through mobile technology can enhance vocabulary mastery among EFL students. Using a mixed-methods design with an experimental framework, the study involved 40 intermediate-level learners from a local English course in Kampung Inggris Pare, selected via purposive sampling. Over the course of four weeks, participants engaged in shadowing activities using mobile applications, including Google Voice Assistant and Duolingo. Data collection combined quantitative measures—pre-test and post-test scores—with qualitative insights drawn from questionnaires and semi-structured interviews. Statistical analysis using a paired-samples t-test produced a t-value of -26.502 (df = 30) and a two-tailed p-value of 0.000, which is well below the 0.05 threshold, confirming a statistically significant improvement in vocabulary performance following the intervention. This suggests that the mobile-assisted shadowing approach effectively supports authentic and meaningful vocabulary learning. Qualitative feedback further indicated that participants benefited from the method’s accessibility, adaptability, and opportunities for repeated practice, although some noted challenges related to audio playback speed and inconsistent internet connectivity. Overall, the findings highlight mobile-based shadowing as a promising and innovative strategy for strengthening vocabulary skills among EFL learners.